The positioning of premium private label brands : a thesis in partial fulfilment of the requirements for the degree of Master of Business Studies in Marketing at Massey University, Palmerston North, New Zealand - Feetham, Pam (Massey University, 2011)
Premium Private Label brands are commanding eye-level shelving space in New Zealand’s supermarkets. With eye-catching packaging and labelling they are attempting to position themselves against established National brands. The question of whether consumers perceive premium Private Label brands as occupying the same perceptual space as these established National brands was the focus of this research. In four FMCG product categories, the positioning of the premium Private Label brand, Select, was compared to that of two National brands and a budget Private Label brand, using on-line surveys. In none of the categories was Select perceived as occupying the same perceptual space as the established National brands, though it was clearly differentiated from its budget counterpart. These findings suggest that, while premium Private Label brands such as Select may never threaten the market position of a dominant National brand, they could compete for the position currently held by weaker National brands in some product categories. This research also confirmed that, generally, New Zealand consumers have positive attitudes towards Private Label brands, but there is some doubt that they fully trust the quality of Private Label brands. Consumers are also more likely to purchase Private Label brands in particular categories, and more likely to do so if they are locally sourced. To avoid any cannibalisation between the premium and budget Private Label brands it is vital retailers maintain the perceptions of quality separation. Communication messages, therefore, need to convey premium Private Label brands’ quality, value for money, and that the ingredients are locally sourced. Retailers could build further premium Private Label brand trust and familiarity by in-store taste trials and free samples.
Keywords: Branding; Marketing; Brand name products; Groceries; New Zealand